Reflections on cultural values approaches to conservation: lessons from 20 years of implementation. Issue 2 (22nd August 2017) - Infield, Mark; Entwistle, Abigail; Anthem, Helen; Mugisha, Arthur; Phillips, Kathryn
Abstract: The natural environment underpins human well-being in diverse and complex ways, providing both material and non-material benefits. Effective conservation requires context-specific understandings of human interactions with, and conceptions of, nature. A focus on how cultural values and norms frame relationships with the natural world can enhance conservation efforts, and can prevent conservation actions undermining local culture and values, providing opportunities to reinforce them instead. Conservation, including the conceptualization and management of protected areas, has the potential to support or undermine these culture–nature relationships. A cultural values approach seeks to identify, understand and integrate considerations of cultural values into the design and implementation of conservation initiatives. Such approaches can realize diverse benefits, including maintaining and enhancing local culture (as a contribution to human well-being), deepening links between communities and conservation activities; facilitating parallel conservation of nature and culture; promoting non-material as well as material natural values; and allowing specific cultural values to inform and drive conservation efforts. Cultural values approaches thus help to enhance the equity, efficacy and acceptability of conservation practice. Fauna & Flora International has implicitly and explicitly acknowledged cultural values within project design and delivery for over 20 years. In 2011 a Cultural Values Programme was established to enhance the role of cultural values of species, places and practices, and of individual and group identities, within conservation. Here we describe our evolving approach to integrating cultural values into conservation practice, provide key lessons learnt, based on specific case studies, and relate these to wider conservation policy and practice.